Study of Organizational Management through Implicit and Explicit Association Measures in Public and Private Management - Maria da Penha Sanches Martins; Gaianê Sabundjian (Brazilian Journal of Radiation Sciences)
This study aims to identify the main characteristics of organizations regarding employees' perceptions, paradigms and prejudices regarding organizational management. Although the Institute of Energy and Nuclear Research (IPEN-SP) and the University of Rio Verde (UniRV - GO) were chosen to conduct this research, this study will present the results of the application of a questionnaire (explicit test) only to a group of IPEN employees. The topics addressed in this research were: bureaucracy, organizational participation, and innovation, among others. Due to the cultural diversity in Brazil and consequently in companies, there are several models of organizational management. However, for the scope of this study, two models are considered: participatory management, focused on innovation, and autocratic management, in which the manager makes decisions unilaterally, without the participation or consultation of employees. These two management models were chosen to stimulate the behavioral profile of employees, that is, it is a way of understanding and identifying the employee's reaction or positioning in a specific situation. The methodology used as a data collection instrument involves the Implicit Association Test (IAT) (unconscious) and explicit (conscious) which is done through a questionnaire. This paper will only present the explicit association test (questionnaire) that was applied to IPEN employees. To apply the implicit association tests, the FreeIAT software will be used, although its application will be done in the next phase of this work as described in this article. The first results of the explicit association test (questionnaire) demonstrate, through the calculation of Cronbach's alpha, its high consistency and reliability.